2008
DOI: 10.1007/s11095-007-9517-8
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Design of Artificial Membrane for Improving the PAMPA Model

Abstract: The new artificial membrane provides an improved PAMPA model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
221
1
7

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(235 citation statements)
references
References 21 publications
6
221
1
7
Order By: Relevance
“…A 96-well donor and accepter plate system pre-loaded with artificial lipid membrane (BD Gentest TM Pre-coated PAMPA Plate) was used. In these plates, each well consists of a polyvinylidene fluoride (PVDF) filter coated with a lipid/oil/lipid trilayer, where the lipid layer is composed of 1,2-dioleoyl-sn-glycero-3-phosphocholine and the oil layer is composed of hexadecane [17]. Acceptor and donor well concentrations were measured using an UHPLC/MS system equipped with a C18 Kinetex (2.10 x 50 mm, 7 μm).…”
Section: Hplcmentioning
confidence: 99%
“…A 96-well donor and accepter plate system pre-loaded with artificial lipid membrane (BD Gentest TM Pre-coated PAMPA Plate) was used. In these plates, each well consists of a polyvinylidene fluoride (PVDF) filter coated with a lipid/oil/lipid trilayer, where the lipid layer is composed of 1,2-dioleoyl-sn-glycero-3-phosphocholine and the oil layer is composed of hexadecane [17]. Acceptor and donor well concentrations were measured using an UHPLC/MS system equipped with a C18 Kinetex (2.10 x 50 mm, 7 μm).…”
Section: Hplcmentioning
confidence: 99%
“…PAMPA models with different lipid compositions have been established; for instance models may consist of a single lipid such as lecithin (Kansy et al, 1998) or mixtures of phosphatidyl-choline, -ethanolamine, -serine, -inositol and cholesterol (biomimetic PAMPA, Sugano et al, 2003). A 20% dodecane solution of a phospholipid mixture (Avdeef et al, 2005), silicone oil and isopropyl myristate (Ottaviani et al, 2006) -which does not occur in vivo -systems of lipid bilayers (Nirasay et al, 2011), and also lipid triple-layers (Chen et al, 2008b) as well as synthetically generated amphiphilic phospholipids (Yu et al, 2015) also exist. An interesting example of a comparison between cell-based and artificial membrane assays was published by Kerns et al (2004), where permeability data from Caco-2 cell monolayer and PAMPA methods was compared.…”
Section: Co-culture and Pathophysiological Modelsmentioning
confidence: 99%
“…The artificial membrane immobilized on a filter is placed between a donor and acceptor compartments (22). Recent studies have described numerous tissuespecific methods that predict the gastrointestinal absorption (23)(24)(25)(26), the penetration through the blood-brain barrier (27)(28)(29) or the barrier function of human skin (30). Our results revealed that modified PAMAM dendrimer with TAT peptide has more capability in the transition of the DNA plasmid through the artificial membrane, as the highest expression of the H5 gene was observed from the delivery system of TAT-conjugated dendrimer compared to the native dendrimer.…”
Section: Discussionmentioning
confidence: 99%